The Influence of Jama’ah Trust and Company Image on the Satisfaction of Jama’ah Umrah Hajj Travel Arminareka - Wiwi Ruwiah (International Journal Labs, 2023)
There are so many Umrah and Hajj service providers in Indonesia, but in the past there have been several cases of embezzlement of funds and fraud against the Jama'ah, thus losing the Jama'ah's sense of trust. Even though there are many such cases, Arminareka Hajj Umrah Travel has consistently maintained the trust of the congregation with its best service so that it has received various awards from several major agencies, this also proves that Arminareka is trusted by the congregation and has a good corporate image. This study aims to determine the effect of congregational trust and company image on the satisfaction of pilgrims traveling Umrah and Hajj Arminareka. This study uses a quantitative research method with a descriptive approach. Data collection techniques in this study used questionnaires and literature studies. The research data were then analyzed using the SPSS program. The results showed that Jama'ah Trust and Corporate Image had a partial and simultaneous significant effect on the Satisfaction of Jama'ah Travel Umroh Haji Arminareka.